Re-Viewing Sumitro’s Policy and Industrial Maturity: Powering Downstream and Manufacturing Industries for Economic Growth and Sustainable Society - Abdullah A Afifi; Hanief Adrian; Evan Azami; Muhammad Farid (IDRIS Darulfunun Institute, 2024)
During the 1950s, Sumitro Djojohadikusumo contributed in a significant manner to the construction of the economy of Indonesia, along with other figures, namely Mohammad Hatta, Sjafruddin Prawiranegara, and Djuanda Kartawidjaja. During this period, Sumitro promoted policies to drive industrialization in Indonesia and self-reliance to transform Indonesia from a colonial economy into a developing nation. Soemitro Djojohadikusumo’s economic policies were pivotal in shaping Indonesia’s post-colonial economy; focusing on production and industrial sovereignty, he emphasized reducing dependency on imports by fostering domestic industries, especially strategic sectors like heavy industry and natural resource processing, which he saw as crucial to national sovereignty. Soemitro also promoted stimulating economic activities through both public investment and private sector engagement, aiming to diversify the economy and drive sustained growth. Many of the challenges Soemitro addressed, such as infrastructural gaps and weak technological readiness, which remain relevant today. This research analyzes to what extent the economic policy shaped by Sumitro impacts Indonesia’s development. This analysis has significance in understanding Indonesia’s contemporary economic planning and trends, particularly in terms of economic policy shaped by the newly elected President of Indonesia, Prabowo Subianto. Analysis of Sumitro’s policy is conducted through the lenses of the industrial maturity concept, which is relevant to growth theory, resource-based view, and development economics. Indonesia’s pursuit of industrial maturity is crucial for transforming its raw resource-based economy into one that competes globally by adding value to domestic production. The need to revitalize manufacturing and strengthen downstream industries is critical for boosting competitiveness and integrating circular economic principles that emphasize sustainability. Soemitro’s vision of empowering society aligns with modern approaches to creating a more inclusive economy. However, infrastructure bottlenecks, a lagging education system, and regulatory complexities continue to slow the progress. Addressing supply chain challenges through regional industrial clustering and focusing on efficiency will be vital for overcoming these barriers. Further empirical research is needed to explore how infrastructure, education reform, and regulatory simplification can enhance Indonesia’s industrial maturity and sustainable economic development.